KEBUTUHAN MODEL BUDAYA PELA GANDONG BERBASIS PEMBANGUNAN DI PROVINSI MALUKU - Wenno, I. H.; Akihary, Wilma (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
Pela Gandong is one of traditions in Maluku based on relation between people of one area to the people in another place that can’t be dismissed by anyone. This topic is interesting remembering the important role the Pela Gandong has. This paper aims to find out a a guidance or models of Pela Gandong based on character building. It is very useful to develop culture education in Maluku province. The result of this research can help goverment to increase social culture and harmony of people, as well as teacher and lecturer in their learning process. Method used in this research was research and development models developed by Borg and Gall with some step i.e. survey, planning for model will be developed, product try out, product developing, product validation, socialitation, and product implementation. The first step of this reserch is a preliminary study conducted to know general perception of people about Pela Gandong through descriptive qualitative approach. The population of this research is all people in Central Maluku province, while sample used in this research were 50 villages. Instruments used were questionaire and interview. Data are collected and analyzed using qualitative approach. The result shows that Pela Gandong is a tradition that can be developed as a means to built characters and education of people that will further contribute to the national development.